2015
DOI: 10.1007/s00464-015-4114-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adhesiolysis for acute small bowel obstruction: systematic review and pooled analysis

Abstract: Laparoscopic surgery for treatment of adhesional SBO improves clinical outcomes and can be performed safely in selected cases with similar rates of bowel injury and reoperation to open surgery. Large scale randomized controlled trials are needed to validate the findings of this pooled analysis of non-randomized data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
2
26
1
4
Order By: Relevance
“…29 However, a systematic review showed that LS for SBO did not increase the risk of bowel injury compared with OS (95% CI 0.24~2.46; p=0.65). 30 Although there was only one case (3.2%) of bowel perforation in the LS group, the incidence of bowel perforation in the present study was lower than those of previous studies. In LS, we insert the first trocar using Hasson' s technique and then introduce the other trocars under direct camera visual guidance.…”
Section: Discussioncontrasting
confidence: 81%
“…29 However, a systematic review showed that LS for SBO did not increase the risk of bowel injury compared with OS (95% CI 0.24~2.46; p=0.65). 30 Although there was only one case (3.2%) of bowel perforation in the LS group, the incidence of bowel perforation in the present study was lower than those of previous studies. In LS, we insert the first trocar using Hasson' s technique and then introduce the other trocars under direct camera visual guidance.…”
Section: Discussioncontrasting
confidence: 81%
“…However, the operative time and the incidence of iatrogenic enterotomy were not reduced. Other previously published systematic reviews [26], [27] also showed the benefit of laparoscopic surgery for SBO. They demonstrated that laparoscopic adhesiolysis is safe and feasible in patients with SBO.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies have reported that the laparoscopic approach did not increase the risk of iatrogenic bowel injury in comparison to open surgery [14], [27], [32]. Recent reports have shown the rate of conversion to be 10–39% [24], [33], [34], [35], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Pooled analyses of non-randomized series suggest significant reductions in mortality, morbidity, wound infections, and length of hospital stay by using laparoscopic approach instead of open surgery. [7][8][9][10] It is acknowledged that these series have high risk of bias owing to obvious selection of less severe cases to laparoscopic approach. 10,11 Although laparoscopic approach is used more frequently than before, 12,13 it has not gained widespread acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The lack of widespread adoption can be appointed to three major reasons: laparoscopic adhesiolysis is technically demanding, 3 it has been associated with higher risk of iatrogenic bowel injury, 12 and, to our knowledge, there is no randomised evidence of benefit and safety. 8,10,11,13 Because of controversy regarding the safety and benefits of laparoscopic adhesiolysis over open approach for small bowel obstruction, we conducted LAparoscopic versuS open adhesiolysis for adhesive Small bowel Obstruction (LASSO) trial. The main hypothesis was that laparoscopic adhesiolysis is feasible treatment of adhesive small bowel obstruction, and it shortens the length of hospital stay without increasing morbidity.…”
Section: Introductionmentioning
confidence: 99%